Kinematic variations between swimming strokes with eyesight deprivation - Kilani, H.; Alkilani, L. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to investigate whether or not swimming eyesight deprivation (SED) affects swimming stroke kinematics, when compared to normal eyesight. Sixteen participants, 12 male and 4 female, swam under three conditions: normal swimming, SED seeing the target, and SED without seeing the target. Data were captured using two Sony digital video cameras, placed perpendicular to the sagittal plane of swimming strokes, and behind the starting point of the swimmers. Stroke length (SL), stroke rate (SR), stroke index (SI), mean time (MT), and mean velocity (MV) were measured. Although swimmers deviated from a straight line, no significance kinematic differences were found between the three swimming conditions.